PHENOTYPIC FEATURES AND CHEMILUMINESCENT ACTIVITY OF NEUTROPHILIC GRANULOCYTES IN THE PATIENTS WITH RENAL CANCER - A. A. Savchenko; A. G. Borisov; A. A. Modestov; I. V. Kudryavtsev; A. V. Moshev; I. I. Gvozdev; O. G. Tonacheva (Медицинская иммунология, 2016)
The aim of our study was to investigate the relationship between phenotype and «respiratory burst» activity of neutrophilic granulocytes in patients with renal cancer. The study included 73 patients with renal cell carcinoma (T3N0M0, clear-cell type) before surgical treatment at the age of 40-55 years. The diagnosis of renal cancer was histologically verified in all the patients. Fifty healthy age-matched persons were involved as a control group. Phenotyping of blood neutrophilic granulocytes was performed by flow cytometry. The respiratory burst in blood neutrophilic granulocytes was evaluated using spontaneous and zymosan-induced luminol- and lucigenin-dependent chemiluminescence. Some changes in relationships between the phenotypic indicators of neutrophils and «respiratory burst» were detected in patients with renal cancer. The patients exhibited a loss of relationship between induction of primary and secondary reactive oxygen species, and numbers of CD11b+, CD62L+, and CD64+ neutrophils. These correlations are detected with HLA-DR+ cell levels, like in control group. The patients’ samples showed a correlation between the superoxide radical synthesis by resting neutrophils, and CD62L expression. These relationships disappear when assessing antigen-induced «respiratory burst» response. The correlations between primary and secondary reactive oxygen species, and the numbers of CD11b+, CD62L+ and CD64+ neutrophils found in healthy people characterize a positive relationship between the «respiratory burst» indexes and activation of cells as reflected by expression of adhesive and functional receptors. It may be assumed that altered relationship between the «respiratory burst» indicators and neutrophil phenotype in the patients with renal cell carcinoma is determined by various factors. Firstly, cancer-associated phenotypic changes of blood neutrophils (decreased content of CD11b+, CD62L+, CD64+, HLA-DR+, and HLA-DR+ CD64+ neutrophils, increased expression of CD16, and HLA-DR receptors) thus, possibly, being connected with intra-tumor migration of the cells. Secondly, the patients show an increase in «respiratory burst» intensity in neutrophils, due to enhanced synthesis of primary and secondary reactive oxygen species, which may be connected to the action of various tumor factors (antigens, regulatory molecules).The relationships revealed between phenotype and «respiratory burst» of neutrophils may specifically characterize immunopathogenesis of kidney cancer and can be used in development of immunotherapeutic approaches aiming to stimulate anti-tumor activity of phagocytic cells.